Exploring entrepreneurial intentions among Sabah's dark tourism operators: A sustainability perspective - Ang, Hong Loong; Suddin Lada; Faerozh Madli; Pang Yeng Yuan; Erick Karunia; Dodi Apriad (IDEAS, 2025)
The sustainable development of dark tourism provides a unique feature for entrepreneurial opportunities. In the state of Sabah, south of the capital city of Kota Kinabalu, committing to sustainable tourism can go a long way in contributing to the growth of economy, culture, and even innovation at the sites of historical interest. Grounded on the Theory of Planned Behavior (TPB), Resource-based View and Stakeholder Theory, this study examines the effects of sustainability orientation, attitude toward self-employment and propensity to innovate on entrepreneurial intention among Sabah’s dark tourism operators. The findings show that attitude toward self-employment and propensity to innovate have positive effects on the entrepreneurial intention. Conversely, sustainability orientation has a negative impact on entrepreneurial intention, indicating that while sustainability continues to be an essential element of tourism, challenges such as regulatory obstacles and operational expenses from sustainability endeavours might lessen entrepreneurial motivation. These findings provide useful recommendations to ensure sustainable and innovative tourism to companies, policymakers, stakeholders and entrepreneurs. This study extends TPB in the niche tourism context, supporting balanced approaches that align entrepreneurship with sustainable-driven policies in the sustainability-based economic and cultural resilience of the region.